(untitled) (Modern Problems of Metallurgy, 2020)
The mathematical model of process of an insertion and expansion of pipe preparation on a parsing press of the parsing line is developed. The ax symmetric current of metal (working environment) between the container plug, a mandrel or an expander is considered. Consistent pattern of distribution of pressure of metal upon a mandrel or an expander taking into account operating conditions in the deformation center is determined. The functionality of axial resistance of a mandrel or expander to a channel of metal at realization of processes of an insertion or expansion of pipe preparation is created. From a condition of minimization of functionality of axial resistance of a mandrel or an expander in a stream of metal the optimum form (calibration) them forming is established.